Empirical study on use of online social networking sites in the Kingdom of Saudi Arabia - Sait, Sadiq M.; Sattar, Karim A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Online Social Networking sites (OSNs) provide Internet users with a useful medium for communication, interaction and collaboration. Reported usage of OSN has pervaded all segments of society irrespective of gender, age, nationality, or educational level. This study provides analysis of how demographic factors affect OSN adoption in the Kingdom of Saudi Arabia. The data represent a nationwide face-to-face survey of over 3000 respondents. Data stratification based on the population distribution across the Kingdom was used to select a portion of the samples from the provinces of the Kingdom. Statistical methods, including descriptive statistical analysis, logistic regression, the measure of association, and chi-square tests, were applied to analyze the data (Haight et al., 2014). OSN variables considered include the extent of usage by younger adults, usage by females, the role of education in the use of OSNs, and the dependence on the use of OSNs on the availability of technology such as mobile Internet. Findings show that education level plays a considerable role for OSN usage, teenagers and young adults use OSN more than others, Saudi nationals use OSN more than expatriates in the Kingdom, and OSN usage depends heavily on the availability of the mobile Internet.